Rheological behavior of different calf sera before, during and after biomechanical testing - Uhler, Maximilian; Schonhoff, Mareike; Nees, Timo A.; Wonerow, Tanja; Nuppnau, Jens; Mantwill, Frank; Kretzer, Jan Philippe; Schröder, Stefan (Lubricants, 2022)
Due to different rheological behavior of human synovial fluid and the test mediums for in vitro examinations, wear tests cannot replicate the in vivo situation completely. The standards for wear testing indicate calf serum as in vitro test medium. However, these standards do not contain precise information on the main constituent components and the rheological properties. In this study, bovine calf serum and newborn calf serum with a protein concentration of 20 g/L, both approved for wear testing defined by the International Organization for Standardization (ISO), were characterized according to their rheological properties to detect differences before and during tribological simulation.